Contracting minors in the sphere of music show business: world experience and Ukrainian challenges - Moskalenko, K. V.; Москаленко, К. В.; Москаленко, Е. В. (Одеса : Юрид. л-ра, 2014)
The article provides general analysis of the legal status of minors engaged in the music show business industry. The author investigates international and national legal framework concerning protection of minor performers and suggests entering amendments into the Law of Ukraine “On сopyright and related rights”.
Moskalenko K. V. Contracting minors in the sphere of music show business: world experience and Ukrainian challenges / K. V. Moskalenko // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 73. – С. 321-327.
Keywords: music show business; minors; contracts; музичний шоу-бізнес; особи, які не досягли повноліття; договори; музыкальный шоу-бизнес; лица, не достигшие совершеннолетия; договоры